1979
DOI: 10.1139/m79-063
|View full text |Cite
|
Sign up to set email alerts
|

A tentative direct microscopic method for counting living marine bacteria

Abstract: Yeast extract (0.025%) and nalidixic acid (0.002%) were added to seawater samples and the samples were incubated for 6 h at 20 degrees C in the dark. Under these conditions, bacterial cells did not divide but grew to form elongated cells that are easily recognized by a direct microscopic method and epifluorescent microscopic technique. The number of cells thus obtained is proposed as a direct cound of viable bacterial cells (DVC). With open ocean samples, DVC was higher than 'viable' plate counts by up to thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
601
3
11

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 888 publications
(631 citation statements)
references
References 0 publications
16
601
3
11
Order By: Relevance
“…A modified technique of Kogure et al [17] was used [5] to enumerate VBNC cells of Listeria monocytogenes.…”
Section: Characterization Of Metabolic Activitymentioning
confidence: 99%
“…A modified technique of Kogure et al [17] was used [5] to enumerate VBNC cells of Listeria monocytogenes.…”
Section: Characterization Of Metabolic Activitymentioning
confidence: 99%
“…Consequently, viable cells will be elongated and can be recognized and counted by microscopy. The addition of nutrients, usually a small amount of yeast extract, is generally required (61). This direct viable count (DVC) method has been applied for detection of viable Vibrio vulnificus (91,105), estimation of viable counts of several gramnegative bacteria in an aquatic environment (15,20,28,29,112,115,127,128,129,150), and detection of viable bacteria in biofilms (151,152).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…It has been demonstrated that VBNC cells are active in metabolism (16,20,53) and are able to recover from their dormant state, becoming metabolically active and fully culturable (26,40,48). Some pathogens in the VBNC state may retain their pathogenicity (8,34,35,37,44).…”
mentioning
confidence: 99%